The Global Diet Quality Score is associated with nutrient adequacy and depression among Vietnamese youths - Nguyen, Phuong Hong; Tran, Lan Mai; Hoang Nga Thu; Deitchler, Megan; Moursi, Mourad; Bergeron, Gilles (Wiley, 2023)
The Global Diet Quality Score (GDQS) has been recommended as a simple diet quality metric that is reflective of both nutrient adequacy and noncommunicable disease outcomes. It has been validated among women of reproductive age (15–49 years) in diverse settings but not specifically among younger women. This paper examines the relationship between the GDQS and nutrient adequacy, anthropometric outcomes, and depressive symptoms among 1001 Vietnamese young women aged 16–22 years. In energy-adjusted models, the GDQS was significantly (p < 0.05) and positively correlated with intakes of protein (ρ = 0.23), total fat (ρ = 0.06), nine micronutrients (calcium, iron, zinc, vitamin C, riboflavin, niacin, vitamin B6, folate, and vitamin A) (ρ = 0.12–0.35), and the mean probability of adequacy of micronutrients (ρ = 0.28). Compared to young women with optimal GDQS, those with low and very low GDQS were two to five times more likely to have a mean probability of nutrient adequacy less than 50% and showed two to three times higher odds for depression. No association was observed for GDQS and anthropometric outcomes. In conclusion, the GDQS performed well in capturing nutrient adequacy and depressive symptoms among Vietnamese young women. Further research is warranted to explore the relationship between diet quality and depression in other settings.